Application of Plastic Strain Method to Determine Threshold Concentrations for Cryoprotective Substances During Saccharomyces cerevisiae Yeast Cell Cryopreservation - Osetsky, A. I.; Kirilyuk, A. L.; Gurina, T. M.; Vysekantsev, I. P. (Problems of Cryobiology and Cryomedicine, 2007)
Plastic strain of glycerol and PEO-1500 frozen aqueous solutions has been studied and an alteration in their plastic characteristics when achieving certain (threshold) concentrations of cryoprotective substances has been established. This change is associated to local closed liquid phase inclusion transition into the through liquid interlayers, that excludes an internal pressure development and corresponding mechanical damages in biological objects being under cryopreservation. This conclusion is confirmed by the experiments on Saccharomyces cerevisiae yeast cell cryopreservation.